Design of durable de-icing, superhydrophobic, superoleophobic coatings - Beemer, Darryl Lewis, author; Kota, Arun K., advisor; Bailey, Travis, committee member; Popat, Ketul, committee member (Colorado State University. Libraries, 2015)
This work looks at the issue of ice accretion on surfaces and efforts to reduce this ice accretion and the subsequent ice adhesion strength in order to make ice removal easier and more cost effective for wider implementation. Ice accretion on various surfaces is a major economic and safety issue for a variety of industries, including air travel, power production and transmission, maritime shipping, and more. While efforts have been taken to diminish ice accretion and subsequent ice adhesion strength, existing technology is limited in its ability to prevent ice accretion in a wide range of conditions and to then have a low ice adhesion strength once ice has accumulated on a surface. With the background of icing and solid mechanics of ice removal in mind, materials were developed to exhibit a low ice adhesion strength while maintaining the durability characteristic of a non-sacrificial coating. After development and testing, it was found that the developed materials exhibited an adhesion strength lower than any currently available technology, with extended durability under both ice removal and mechanical abrasion conditions. As a secondary effort, an initial exploration into the development of durable superomniphobic surfaces was performed in order to reduce and/or prevent adhesion of water-based paint and a low surface-tension fluid to various surfaces. Development of a variety of surface types (spray coated layered and mixed surfaces, etched stainless steel surfaces, and more) was performed, with initial results providing an encouraging path forward for future development of this durable coating work.
Keywords: coating; durability; superoleophobic; de-ice; adhesion; superhydrophobic